Aplikasi Bahan Ajar Bahasa Inggris Berbasis Android di Politeknik Negeri Fakfak - Magfirah, Titing; Arridha, Riyadh; Lanja, Sesilia; Rumanama, Nuryanti (Sinkron : jurnal dan penelitian teknik informatika, 2021)
One of the ways to attract students' interest in learning English is to use interactive teaching materials. However, the teaching materials used at State Polytechnic of Fakfak are still in the form printed materials which seem inefficient to be used during the Covid 19 pandemic because the all the teaching process is online. Therefore, one of the solutions to implement mobile learning. Using mobile learning provides the users accessing material through smartphones and learning through mobile learning applications anywhere and anytime. This study aims to develop teaching materials in the form of an Android-based English Learning Application at Department of Informatics Management at the State Polytechnic of Fakfak, West Papua. The method used in this study is the Waterfall method, where a software development model is carried out sequentially, which means that one stage is carried out after the previous stage is completed. With the teaching materials in the Android-based English course, it can help the educators to carry out their duty as a lecturer to handle learning process during the Covid-19 pandemic.  The result of this study is an Android-based English Learning Application that is functionally tested using the Black Box method. Based on the test results, the application is functioning properly. This is proved by the feasibility test using distributed questionnaires to 40 students of the Department of Informatics Management. There are 96% of students stated that the application can be operated easily and is satisfying